The Trend of Delivery Room Utilization and Delivery Profiles in Obstetric Patients at RSU. Premagana 2021-2022. - Bayuningrat, I Gusti Ngurah Made; Pradnyaningrat, I Gusti Ngurah Andika Manik; Dwinanta Kartha, Ida Bagus Bramantya (Fakultas Ilmu Kesehatan, 2024)
Healthcare facilities providing Obgyn services are hospitals. The delivery room provides healthcare services for Obgyn patients. The location of this research is at Premagana General Hospital in Gianyar Regency. The problem under investigation is related to the trend of delivery room utilization and childbirth profiles of Obgyn patients at Premagana General Hospital in 2021-2022, as there has been no existing data or research conducted on the prevalence of these cases. The aim of this research is to provide solutions and basic data availability to address the issue of the availability of facilities and infrastructure supporting services. The method used involves secondary data from Obgyn patients' medical records in the delivery room, which is then tabulated, summarized, and quantified based on the types of cases. Results: The trend of delivery room utilization and childbirth profiles of Obgyn patients in 2021 showed that Cesarean Section (CS) was 78,5%, CS with the Woman's Operative Method (CS-WOM) was 9,89%, Normal Delivery was 1.1%, Premature Birth, Vacuum Extraction, Curettage (DC), Hysterectomy, Placental Rest, Preeclampsia was 0,04%, while in 2022, it was as follows: Cesarean Section (CS) 82,5%, CS with Woman's Operative Method (CS-WOM) 6,97%, Normal Delivery 10,5%, Vacuum Extraction, Curettage (DC) 0.09%. The majority were CS followed by CS-WOM, Normal Delivery, and the least common procedures were Premature Birth and Vacuum Extraction. The most common operative procedure CS was performed in obstetric and gynecological cases at Premagana General Hospital, covering 78,5% of cases in 2021 and 82,5% in 2022.